Pembelajaran Ansambel Musik Pada Kelas XI IPA 3 Di MAN 2 Padang - Putri Nabila Nurfaizah; Harisnal Hadi (Institut Nalanda, 2023)
This study aims to describe the implementation of music ensemble learning in class XI Science 3 at MAN 2 Padang. This type of research is qualitative research with descriptive methods. The instruments in this study are the researchers themselves and are assisted by supporting instruments in the form of stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The data in this study used primary data and secondary data. The steps of analyzing data are collecting data, identifying data, classifying data, describing data and inferring data. The results showed that in learning music ensembles in class XI Science 3 at MAN 2 Padang, teachers only focused on presenting pianica ensemble music. In the implementation of this ensemble music learning, teachers conduct learning not in accordance with the RPP (Learning Implementation Design) that has been made. However, the RPP made is in accordance with the 2013 curriculum. Ensemble music learning in class XI Science 3 at MAN 2 Padang went well. Although teachers lack mastery in the art of music, teachers can condition learning by providing simple practical materials to students and teachers also use peer tutor methods so that the learning of this ensemble music runs well.